Identification and Antibiotic Susceptibility Profiling of Bacteria Isolated from Four selected Rivers and Six Tributaries in Ibadan Metropolis, Oyo-State, Nigeria (2018)
Water is one of thè major resources necessary for thè maintenance of life on earth. Among thè pathogens disseminateci in water sources are enteric pathogens such as enterotoxigenic Escherichia coli, Shigella spp., Salmonella spp., and thè presence of these organisms are responsible for a variety of diseases like diarrhea, dysentery, and enteric fever. This study was aimed to identify and determine antibiotic susceptibility profile of bacteria isolated from selected rivers in Ibadan metropolis. Thirty water samples were collected from three different sites (upstream, midstream and downstream) of four selected main rivers and six tributaries, thè main rivers are: Onibu-ore river, Kudeti river, Ogunpa river and Ona river, while thè tributaries are: Gege river, Awolowo river, Orogun river, Orni river, Tabieleshin river and Eleyele river. The samples were routinely screened for bacteria using MacConkey and blood agar plates. These bacterial isolates were identified biochemically and were further subjected to antibiotic susceptibility test. All thè tests performed in this study were analyzed using tables. From thè thirty water samples of thè ten selected rivers screened in duplicates in this study, forty-two isolates belonging to eleven bacteria genera of different percentage distribution were identified. These isolates also showed different antibiotic resistance rates and pattems. Of all thè bacteria isolates obtained in this study, only Enterobacter species was not multi-drug resistant. This study detected thè presence of different bacteria isolates in drinking river water from ten selected rivers in Ibadan. It was able to confimi thè presence of E. coli in water and further discovered other bacteria such as Arthrobacter species in water.